Realization of Colored Multicrystalline Silicon Solar Cells with SiO2/SiNx:H Double Layer Antireflection Coatings - Minghua Li (International Journal of Photoenergy, 2013)
We presented a method to use SiO2/SiNx:H double layer antireflection coatings (DARC) on acid textures to fabricate colored multicrystalline silicon (mc-Si) solar cells. Firstly, we modeled the perceived colors and short-circuit current density (Jsc) as a function of SiNx:H thickness for single layer SiNx:H, and as a function of SiO2 thickness for the case of SiO2/SiNx:H (DARC) with fixed SiNx:H (refractive index n=2.1 at 633 nm, and thickness = 80 nm). The simulation results show that it is possible to achieve various colors by adjusting the thickness of SiO2 to avoid significant optical losses. Therefore, we carried out the experiments by using electron beam (e-beam) evaporation to deposit a layer of SiO2 over the standard SiNx:H for 156×156 mm2 mc-Si solar cells which were fabricated by a conventional process. Semisphere reflectivity over 300 nm to 1100 nm and I-V measurements were performed for grey yellow, purple, deep blue, and green cells. The efficiency of colored SiO2/SiNx:H DARC cells is comparable to that of standard SiNx:H light blue cells, which shows the potential of colored cells in industrial applications.